Strategies to Improve Brand Awareness Through Social Media Marketing - Nadirah Azizan; Hanis Zulaika Ismail@Chik; Aida Maisarah Fadzli; Nor Irvoni Mohd Ishar (Universitas Airlangga, 2023)
Objective: The objective of this study consists of; 1) To understand the current situation of an Event Organizer Company (EOC), 2) To examine the influences between Electronic Word-of-Mouth (EWOM), advertisement, interaction, and customization, with brand awareness among the EOC clients, and 3) To recommend strategies to increase brand awareness among the EOC clients. Design/Methods/Approach: Using the applied research approach, a situational analysis was used to gather information before survey questions were used to capture data. In this correlational study, which takes a quantitative method, individuals are the analytical unit. This research involved 108 clients in total. A 25-item questionnaire with a 5-point Likert scale was given to clients living in the Klang Valley in order to gather data. This research used regression analysis to analyze the data and two strategic tools (SWOT Analysis & TOWS Matrix) for data analysis. Findings: The results show that EWOM, advertising, and interaction have a positive influence on brand awareness. In contrast, the influence of customization on brand awareness was found to be statistically insignificant. Originality: This study's value lies in the fact that researchers examined the factors that influenced the EOC's brand awareness and provided recommendations to the company, such as increasing audience engagement and creating appealing social media content and advertisements. This research paper highlights a specific problem within the company in the event management industry that has not been addressed in prior studies. Research Practical: The four critical factors in this research are EWOM, advertisement, interaction, and customization. The results of this study can be used as guidelines, and the researchers' suggested strategies can help the EOC increase awareness of its brand.